Комплекс археологических объектов в балке Еди-Евлер и ее ближайших окрестностях (краткие итоги исследований 2003-2007 гг.) - Лысенко, А.В.; Тесленко, И.Б. (Археологический альманах, 2012)
Балка, известная под тюркоязычным названием Еди-Евлер (Едиэв), располагается на юго-восточном склоне горы Южная Демерджи. Она образована водотоками из оврагов Чакудан-Дере, Фындык-Дере, АгачДере, Хайназ-Дереси. Более или менее стабильный водоисточник – карстовый родник Тапшан-Гя. Верховья протекающего по балке ручья носят название Кобетке. The brief results of archeological investigations in the Edi-Evler valley and its nearest environs (Semidvorie village, Alushta, Crimea) spent by the Mountain-Crimean expedition (NAS of Ukraine, IA, Crimean branch) in 2003, 2006 and 2007 are presented in publication. Results of researches allow confirming, that this territory was used by Taurica population during an epoch of the late bronze and then during the Middle Ages at least from VII century a.c. There is the necropolis of «Suuk-su» type in its bottom part. It’s the last northeast ones among known monuments of such kind. In second half of 8-9th – first half of 10th centuries there were a large settlement (a total area near 5 hectares) with two potteries productions centers and two or three Christian temples. We have no data how the Edi-Evler valley has been used after middle 10th century. There are only remains of small unidentified construction of the second half of 14-15th on the ruins of earlier medieval temple on a Tuzluk hill.